PENINGKATAN KETERAMPILAN MENYIKAT GIGI MENGGUNAKAN MEDIA PICTURE AND PICTURE PADA ANAK PRASEKOLAH KOTA BANDUNG - Damayanti, Dea Ayu Fitria; Praptiwi, Yenni Hendriani; Laut, Deru Marah; Nurnaningsih, Hera (Poltekkes Kemenkes Bandung, 2024)
Education about goods and correct brushing skills is crucial to educate preschoolers in instilling daily habits because the age of preschool children's the golden age or the right time to educate. The method used to improve brushing skills is to use picture and picture media. Other than terms purpose on determine the effectiveness of picture and picture media in improving proper brushing skills in preschool children in Binong Village, precisely at PAUD Cempaka and PAUD Al Ma'mur. The research method used was a one-group pretest-postest system focused on sampling of 52 children from both preschools. Assessment of brushing skill was observed two times, before counseling (pre-test) and after counseling using picture and picture media (post-test). The normality test using Kolmogorov-Smirnov showed a p-value < 0.05; this mean distributed value is abnormal. Thus, hypothesis testing uses a non-parametric test (Wilcoxon signed-rank test). The average result of the proper brushing skill score before and after counseling using picture and picture media has increased, with a significant difference in the average score of the exact brushing skills using picture and picture media (p-value 0.000 < 0.05), so that there is effectiveness in the picture and picture media in brushing skill in preschool children in Binong Village, Bandung City.